The Effect of Profitability, Liquidity, and Leverage on Financial Distress in Property and Real Estate Companies Listed on the IDX - Adania Azzahra; Agustin Ekadjaja (Golden Ratio of Auditing Research, 2026)
This study examines the effect of profitability, liquidity, and leverage on the probability of financial distress in property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024. Employing a quantitative approach with a causal design, this study uses secondary data drawn from annual and financial reports of 75 companies, yielding 225 panel observations. Financial distress is measured using the modified Altman Z-Score, transformed into a binary dummy variable, while profitability is proxied by Return on Assets (ROA), liquidity by the Current Ratio (CR), and leverage by the Debt-to-Assets Ratio (DAR). The data are analysed using binary logistic regression with panel data, estimated via EViews 10. The results reveal that profitability has a significant negative effect on financial distress, confirming that higher asset returns reduce distress risk. Liquidity also exerts a significant negative effect, indicating that adequate current assets protect companies from short-term payment failure. In contrast, leverage has a significant positive effect, demonstrating that a greater reliance on external debt amplifies financial vulnerability. Collectively, the three variables explain 55.96% of the variation in financial distress probability, with an overall model prediction accuracy of 87.56%. These findings provide practical guidance for management, investors, and regulators in assessing financial health risks within Indonesia's property and real estate sector.